Answer:
<u>37/8</u>
Step-by-step explanation:
we are going to create 5 1/2 into an improper fraction for now, so it is easier to manipulate.
5 1/2 = 11/10
in order to find the answer, we need to set them both to a common denominator(we need to make sure they have the same denominator so it is easier to subtract)
11/2 if we just take 1 of the cups that Abby made and subtract that by 7/8 that give us the answer
11/2 - 1 = 9/2
we will now us the cup we subtracted from that and "give it to the kids"
1 = 8/8
so
8/8 - 7/8 = 1/8
so we have 1/8 leftover from that cup, so we can add that back
since 1/8 is a hard number to just add off the top of your head, we can just change the denominator of 9/2 into 8 instead of 2:
9/2 = 36/8
so
1/8 + 36/8 = 37/8
so since 37/8 cannot be simplified anymore, the answer is
<u>37/8</u>
Answer:
(3x+1)(x+3) is the factorised form for the expression.
Step-by-step explanation:
:3
x
2
+
10
x
+
3
We can Split the Middle Term of this expression to factorise it.
In this technique, if we have to factorise an expression like
a
x
2
+
b
x
+
c
, we need to think of 2 numbers such that:
N
1
⋅
N
2
=
a
⋅
c
=
3
⋅
3
=
9
and,
N
1
+
N
2
=
b
=
10
After trying out a few numbers we get:
N
1
=
9
and
N
2
=
1
9
⋅
1
=
9
, and
9
+
(
1
)
=
10
3
x
2
+
10
x
+
3
=
3
x
2
+
9
x
+
1
x
+
3
=
3
x
(
x
+
3
)
+
1
(
x
+
3
)
(
3
x
+
1
)
(
x
+
3
)
is the factorised form for the expression.
is the factorised form for the expression.
The answer is B) add 1.25 and 2.70 and subtract that from 10.00
G2=g1*2
g3=g1*2²
196=x*4
/4 /4
49